Does prolonged standing at work among teachers associated with musculoskeletal disorders (MSDs)? - Alias, Ayuni Nabilah; Karuppiah, Karmegam; How, Vivien; Perumal, Velu (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
In order to accomplish a wide range of duties and responsibilities that may be done under unpleasant working conditions, prolonged standing posture is common with school teachers. Nevertheless, standing upright for a long time or otherwise regarded as prolonged standing frequently contributes to body pain and discomfort, muscle fatigue and even health problems such as musculoskeletal disorders (MSDs). The aim of this paper is to review MSDs arising from prolonged standing and spread information on existing ergonomic and non-ergonomic interventions to alleviate prolonged standing discomfort. Systematic review on prolonged standing school teachers with specific keywords were recognized to discover the appropriate studies and information in a systematic search. The informations in this review may be helpful to guide teacher, school management and researchers to implement the suitable interventions in order to minimise the health issue due to MSDs among school teachers.